Business-Model of the Organization in Economy of Knowledge - S. N. Kukushkin (Вестник Российского экономического университета имени Г. В. Плеханова, 2018)
On the basis of the pattern of organization business-model the author puts forward business-models of the organization of the quadro-sector of economy of knowledge. Mainly, university is an organization of this sector and it carries out education and academic activity. Therefore, a typical business-model was designed for it and it was called 'mirror'. University activity as a business organization has always had certain distinguishing features. These features imply, first of all, that future specialist during the whole period of training acts both as a key resource and a customer and, finally as a value offer. The next important feature is connected with the fact that knowledge is not only transferred in the university but it is developed there. In economy of knowledge the university is assigned a part of a researcher and an impetus to development. At the same time, the university, which can train personnel for other industries and develop knowledge, can also in cooperation with other organizations develop knowledgeintensive products. In this case another business-model is necessary, which was called 'refraction'. Its own business-model was developed for the research organization. The article reveals the content and specific features of each block of advanced business-models. And finally, the author formulated the problem that should be resolved by economic science due to shaping of economy of knowledge.